The commodity nature of labour-power - Starosta, Guido (2016)
Some recent Marxist contributions, among them the so-called New Solution to the transformation problem, call into question the idea of labour-power as a fully-fledged commodity. Yet, the rejection of the commodity nature of labour-power compromises Marx´s whole explanation of the origin of surplus-value on the basis of the exchange of equivalents. It can be shown, however, that it is possible to offer a positive case for the commodity-nature of labour-power which is consistent with Marx´s broader dialectical investigation of the determinations of the value-form. This requires building upon the arguments that Marx explicitly put forward in his economic works, but also going beyond them, albeit on the basis of those arguments themselves. Furthermore, this novel approach that treats the reproduction of labour-power as a commodity determined by the self-valorisation of capital proves to be very valuable to shed light on two classic Marxist controversies, namely: the debate on domestic labour and the one on skilled labour.